Efficacy of Progesterone Receptor Antagonist for Treatment of Pyometra in Bitches - Chandrakar, Upasana; Tiwari, Rajendra P.; Poyam, Mahesh R.; Mishra, Girish K. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present study aimed to assess the efficacy of Progesterone Receptor Antagonist for Treatment of Pyometra in Bitches. The  present research work was carried out on a total of 12 bitches diagnosed with pyometra. The animals were randomly assigned to  two treatment protocols, with 6 animals in each group. In Group I, bitches were administered only with supportive therapies, i.e. fluid  therapy, cloprostenol, and ceftriaxone. In Group II, bitches were administered with progesterone receptor antagonist (mifepristone) and  supportive fluid therapy as in Gr-I. The physiological, hematological, and biochemical parameters were evaluated on days 0, 4th, and 8th  of treatment. The recovery rate of treated bitches was assessed by ultrasonography post-treatment. There was a significant increase in  the mean PCV and a decrease in leucocyte count in group II on day 8. After treatment, the mean serum globulin and creatinine level  reduction was significant (p
Keywords: Bitch; Mifepristone; Prostaglandin; Pyometra